The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1039/d1nj06015e
|View full text |Cite
|
Sign up to set email alerts
|

Oxo(corrolato)vanadium(iv) catalyzed epoxidation: oxo(peroxo)(corrolato)vanadium(v) is the true catalytic species

Abstract: de Visser et al. have demonstrated theoretically that although vanadium(IV)-oxo complexes are slow oxidants, however in the presence of H2O2, it has generated a side-on vanadium-peroxo complex, which is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 70 publications
1
16
1
Order By: Relevance
“…1 exhibited comparatively better TOF values than those reported in the literature, and 2 was found to be substantially more efficient and thus a very strong catalyst for the selective epoxidation of olefins under ambient reaction conditions. Some recent vanadium corroles in the literature have shown better TOF values than catalyst 1 or 2 , but in some cases, TOF values are very low as 400 h –1 with some olefins for these vanadium corroles . Also, these molybdenum corrole catalysts employed in the current study are still better as they complete the reaction in 2 h with good TOFs using the green methodology than previously reported molybdenum corrole catalysts .…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…1 exhibited comparatively better TOF values than those reported in the literature, and 2 was found to be substantially more efficient and thus a very strong catalyst for the selective epoxidation of olefins under ambient reaction conditions. Some recent vanadium corroles in the literature have shown better TOF values than catalyst 1 or 2 , but in some cases, TOF values are very low as 400 h –1 with some olefins for these vanadium corroles . Also, these molybdenum corrole catalysts employed in the current study are still better as they complete the reaction in 2 h with good TOFs using the green methodology than previously reported molybdenum corrole catalysts .…”
Section: Resultsmentioning
confidence: 48%
“…Some recent vanadium corroles in the literature have shown better TOF values than catalyst 1 or 2, but in some cases, TOF values are very low as 400 h −1 with some olefins for these vanadium corroles. 31 Also, these molybdenum corrole catalysts employed in the current study are still better as they complete the reaction in 2 h with good TOFs using the green methodology than previously reported molybdenum corrole catalysts. 28 Earlier, it has been reported that other metallocorroles are good catalysts, but the TOF values are very low.…”
Section: Scheme 2 Products Of the Oxidative Bromination Of P-cresol U...mentioning
confidence: 58%
See 2 more Smart Citations
“…[38] To this end, a wide variety of vanadium complexes with distinct ligands (starting from [VO-(acac) 2 ] and extended to involve the complexes of various Schiff base or salen kinds of ligands) have been widely used effectively in epoxidation reactions. [38] In addition, a few oxime-based vanadium(IV) complexes are also successfully employed as catalysts for olefin epoxidation. [39,40] Nevertheless, these vanadium(IV)-oxime complexes exhibit limited catalytic activity, and their preparation routes are sophisticated and expensive.…”
Section: Introductionmentioning
confidence: 99%